(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The article is reported on the role of religion and its influence in civil society. The most important event in this article is the overall concept of civil society and reporting its description and differences in Kazakhstan, and the role of religion and its interaction in the formation of civil society. The civil society is the appearance of development and stability of the countries and its image is the most important factor for the state. Because, many social groups and other communities around the stable relations system interaction to be effective member of the civil society, and is the basis of successful inevitable management. At the same time, the role of religion in the formation of civil society in this regard should be recognized that the current reviews of the revival of the modern features that are known. Problems that are studied in this article are devoted as the topic of the day. Due to the fact that global religious overtones are dominated by political events and conflicts, acts of terrorism are happening now. Thus, this is the very important event that the religious situation in the Republic of Kazakhstan, which is relevant to the analysis in process of civil society formation and religion in theory, has a clear scientific basis. Researchers believe that the issue is still should be the subject of basic research. Key words: religion, civil society, radicalism, right, tolerance, politics, islam, tradition, unconventional islamic flows.